A study of dosimetric characteristics for in vivo dosimetry with cylindrical n-type Isorad diode. Issue 1 (22nd April 2013) - Islam, Kashif; Haque, Asdar; Muhammad, Khan; Murad, Sohail; Hussain, Muzaffar; Ashfaq, Asma; Islam, Atif
Abstract: Background and purpose: The objective was to determine diode characteristics before actual dose verification on human phantom and patients. Materials and methods: The reliability and stability of equipment, signal stability, precision, dose response linearity, field flatness, perturbation of radiation dose, plastic to water conversion factor ( K pl ), ionisation chambers (ICs) and diode calibration were determined. Correction factors for tray ( CF tray ), wedge ( CF wedge ), field size ( CF FS ), SSD ( CF SSD ), angle ( CF angle ) and block ( CF block ) were found. Patient dose monitor, Isorad diode (n-type) and IC (PTW Frieburg), Co-60 unit (Theratron), ATOM Adult male human phantom (Model 701-D, CIRS) were used. Results and conclusion: Good signal stability, precise data, and linear dose response, variation of 0·500% and 5·000% in field flatness and perturbation tests, respectively, were noted. K pl was 1·006 for IC PTW Frieburg TW30013, 0114. The diode calibration factor was 0·989. CF tray, CF FS, CF SSD, CF angle, CF block were 1·001, 1·001, 0·997, 1·006 and 0·990, respectively. CF wedge were 1·024, 1·030 and 1·038 for 30°, 45° and 60° wedges, respectively. The verification of above correction factors (CFs) on Nasopharynx and lung of human phantom was also done.